Estimated viability of greenhouse cooling technologies for growing a tomato crop under various climates - Yang, Yating; Guo, Shirong; Chen, Yongsheng (International Journal of Agricultural and Biological Engineering, 2021)
The viability of fan and natural ventilation, combined with evaporative cooling, was investigated using a simulation model and weather data for thirty-seven locations in the world (mostly in China). And the geographical distribution pattern of viable cooling technologies was examined in China. The model used was based on a simplified steady-state heat balance of a greenhouse, and weather data were from corresponding meteorological organizations. The evapotranspiration coefficient used two values of 0.5 and 1.0, and ventilation rates for natural ventilation were based on two empirically constructed equations. The results suggested that the viability of various cooling technologies depended largely on local weather, although evapotranspiration coefficient and ventilation characteristics of natural ventilation also played important roles. Some locations were sensitive to evapotranspiration coefficient and ventilation rate while some were not. The locations which were not sensitive to evapotranspiration coefficient and ventilation rate could choose the most economical technology to meet the cooling minimum, but these locations which were sensitive required evaporative cooling and/or forced ventilation. A detailed examination of the geographical pattern of viable cooling technologies was conducted for China. The results suggest that high altitude general provides a cooling advantage.Keywords: climate, cooling, evaporative cooling, greenhouse, ventilation, viability, tomatoDOI: 10.25165/j.ijabe.20211404.6134Citation: Yang Y T, Guo S R, Chen Y S. Estimated viability of greenhouse cooling technologies for growing a tomato crop under various climates. Int J Agric & Biol Eng, 2021; 14(4): 90–95.